Digital integration between hospitals and local health authorities for enhanced vaccination coverage among frail patients: the CareVax study protocol - Lontano, Alberto; Regazzi, Luca; Tona, Diego Maria; Di Pumpo, Matteo; Porcelli, Martina; Cacciuttolo, Maria Gabriella; Parente, Paolo; Gasbarrini, Antonio; Grandaliano, Giuseppe; Panocchia, Nicola; Lopetuso, Loris; Pasciuto, Tina; et al. (Frontiers in Public Health, 2025)
BackgroundThe 2022–2025 Italian Plan for vaccine prevention (PNPV), recognizes vaccine-preventable diseases (VPDs) as significant contributors to mortality, morbidity, and healthcare expenditure. The digitalization of the national vaccine registry is underway. Initiatives aimed at enhancing digital integration between hospitals and territories are limited, and there is still a gap in the development of automated systems for identifying patients who could benefit from vaccinations directly offered from hospitals.MethodsAdult frail patients who access the hospital will be recruited over 4 years, following the acquisition of informed consent. With the assistance of a privacy-preserving automated algorithm, electronic hospital and vaccination records will be utilized to assess eligibility for vaccinations against SARS-CoV-2, Herpes Zoster, Influenza, Streptococcus pneumoniae, and Hepatitis B. Eligible patients will be invited to schedule a vaccination appointment and will be asked to fill in a questionnaire evaluating patient-reported experience measures (PREMs). Outcomes of interest are the feasibility of the pathway, patients’ satisfaction and concerns with it, and its impact on vaccination coverage.Ethics and disseminationThe study has been approved by the ethics committee of the “Fondazione Policlinico Universitario Agostino Gemelli” -FPG- (comitato.etico@policlinicogemelli.it), with approval number 5819. Furthermore, it has been published on ClinicalTrial.gov with the approval number NCT06127563. The results of the study will be disseminated via conference presentations and peer-reviewed publications.Clinical trial registrationClinicalTrials.gov, identifier NCT06127563.